Case report: A case of SLC26A4 mutations causing pendred syndrome and non-cystic fibrosis bronchiectasis - Kang Zhu; Yingkang Jin (Frontiers Media S.A., 2023)
The SLC26A4 gene encodes the transmembrane protein pendrin, which is involved in the ion transport of chloride (Cl-), iodide (I-) or bicarbonate (HCO3-). Mutations in the SLC26A4 gene alter the structure and (or) function of pendrin, which are closely related to Pendred syndrome. What's more, researchers have demonstrated in vitro that mutations of SLC26A4 cause acidification of airway surface fluid (ASL), reduce airway defense, and increase the thickness of ASL. In the context of infection, it may lead to chronic inflammation, destruction of airway wall architecture and bronchiectasis. However, there is no case report of bronchiectasis caused by SLC26A4 gene mutations. Here, we describe the first case of Pendred syndrome and non-cystic fibrosis bronchiectasis in a child possibly caused by SLC26A4 mutations. We remind clinicians to pay attention to the possibility of bronchiectasis in patients with SLC26A4 gene mutations.